Study of the combined effect of thermal storage and sunlight concentration for a solar distiller - Lee, Shau Meng (2024)
Solar distillation is one of the methods used for water desalination. It involves only evaporation and condensation process to remove impurities from the saline water and produces clean water. The only source of energy required by solar distiller is solar thermal energy, which makes it an ideal choice for rural areas that is lack of advanced technologies. The performance of the solar distiller can be improved by implementing thermal storage and sunlight concentration devices. Thermal storages made from phase change materials are commonly used. However, the low thermal conductivity of phase change materials reduces the efficiency in storing and releasing heat energy. Therefore, conductive particles such as aluminium is added into the phase change materials to increase the thermal conductivity. Besides, the Fresnel lens with higher concentration ratio is able to concentrate more solar irradiance towards the solar distiller. Experiments were conducted to find out the optimal ratio of paraffin wax to aluminium scraps as a thermal storage and the optimal Fresnel lens concentration ratio. Saline water of 35000 ppm was used in this research to imitate the salinity of seawater. The optimal ratio was found to be 8:2. It increased the productivity and efficiency of the basic solar distiller by 93.06% and 10.74% respectively. The Fresnel lens with concentration ratio of 25.00 was implemented onto the solar distiller with thermal storage had further improved the productivity and efficiency of the basic solar distiller by 506.39% and 25.89% respectively. The clean water was produced with a total dissolved solids value ranges from 69 ppm to 92 ppm which complied to the safe water drinking standard by World Health Organisation (WHO) which stated that the total dissolved solids value should be lower than 500 ppm for safe drinking water.